IMPLEMENTASI SELF MONITORING IRON SUPLEMENTATION CARD YANG SERVICE EXCELLENT PADA IBU HAMIL UNTUK PEMANTAUAN KEPATUHAN KONSUMSI TABLET TAMBAH DARAH PADA IBU HAMIL DI DESA BANGUN REJO KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG PROVINSI SUMATERA UTAR - Fauzianty, Ariska; Friza Novita Sari; Yesica Geovany Sianipar; Sonia Novita Sari; Rasmi Manullang; Nova Isabella Mariance Br Napitupulu (Jurnal Pengabdian, 2025)
ABSTRACT Anemia during pregnancy remains a significant public health issue with a high prevalence in Indonesia. One of the primary efforts to prevent anemia is through the consumption of iron supplementation tablets (Tablet Tambah Darah/TTD). However, adherence among pregnant women to TTD consumption remains low due to insufficient monitoring and suboptimal support from healthcare services. This community engagement activity aimed to improve TTD adherence among pregnant women through the implementation of a self-monitoring card combined with a patient-centered excellent service approach by healthcare workers. The activity was conducted in Bangun Rejo Village, Tanjung Morawa Subdistrict, Deli Serdang Regency, involving 15 pregnant women in their second and third trimesters. The intervention consisted of educational sessions, distribution of TTD self-monitoring cards, and support from community health cadres. Evaluation was carried out using a pre–post test design, observation of card usage, and structured interviews. There was a significant improvement in TTD adherence, with the proportion of pregnant women consuming ≥6 tablets per week increasing from 33% to 83% after the intervention. The self-monitoring card proved effective in enhancing awareness and engagement of both mothers and their families. The implementation of excellent service also contributed to increased satisfaction with maternal health services. In conclusion, the combination of a self-monitoring card and excellent healthcare service is proven to be effective in improving TTD adherence among pregnant women. This intervention is recommended for broader implementation as part of anemia prevention efforts in maternal health programs. KEYWORDS Self Monitoring; Iron Supplementation Card; Excellent Service; Compliance; Blood Supplement Tablets ABSTRAK Anemia pada kehamilan masih menjadi masalah kesehatan masyarakat dengan prevalensi yang tinggi di Indonesia. Salah satu upaya pencegahan anemia adalah melalui konsumsi Tablet Tambah Darah (TTD). Namun, kepatuhan ibu hamil dalam mengonsumsi TTD masih rendah akibat kurangnya pemantauan dan dukungan pelayanan yang optimal. Kegiatan ini bertujuan untuk meningkatkan kepatuhan konsumsi TTD pada ibu hamil melalui implementasi kartu pemantauan mandiri yang dikombinasikan dengan pendekatan pelayanan prima dari tenaga kesehatan. Kegiatan dilaksanakan di Desa Bangun Rejo, Kecamatan Tanjung Morawa, Kabupaten Deli Serdang dengan melibatkan 15 ibu hamil trimester II dan III. Intervensi dilakukan dalam bentuk edukasi, distribusi kartu pemantauan konsumsi TTD, pendampingan kader. Evaluasi dilakukan melalui pre–post test, observasi penggunaan kartu, dan wawancara terstruktur. Terdapat peningkatan signifikan dalam kepatuhan konsumsi TTD, dari 33% menjadi 83% ibu hamil yang mengonsumsi ≥6 tablet per minggu setelah intervensi. Penggunaan kartu pemantauan efektif dalam membangun kesadaran dan keterlibatan ibu serta keluarga. Pelayanan prima yang diterapkan juga meningkatkan kepuasan ibu terhadap layanan kesehatan. Kombinasi kartu pemantauan mandiri dan pelayanan prima terbukti efektif dalam meningkatkan kepatuhan konsumsi TTD pada ibu hamil. Intervensi ini direkomendasikan untuk diterapkan secara lebih luas dalam upaya pencegahan anemia kehamilan. KATA KUNCI Kartu Suplementasi Zat Besi; Kepatuhan; Pelayanan Prima; Pemantauan Mandiri; Tablet Tambah Darah